164k views
1 vote
2.4(x - 6) = -5.6x + 8​

1 Answer

6 votes

Let's solve your equation step-by-step

2.4(x-6)=-5.6x+8

Step 1: simplify both sides of the equation

2.4(x-6)=-5.6x+8

(2.4)(x)+(2.4)(-6)=-5.6x+8 (distribute)

2.4x+-14.4=-5.6x+8

2.4x-14.4=5.6x+8

Step 2: Add 5.6x to both sides.

2.4x-14.4+5.6x=-5.6x+8+5.6x

8x-14.4=8

Step 3:Add 14.4 to both sides

8x-14.4+14.4=8+14.4

8x=22.4

Step 4 : Divide both sides by 8

8x/8 =22.4/8

Answer : x=2.8

User Tzelleke
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.